Sobre cuándo se inicia un proceso - Priori Posada, Giovanni F. (2015)
This article explains when a judicial process starts, involving the exercise of fundamental procedural rights under the theory that is handled. Analyzing the current Peruvian legislation allows the author to conclude what concept or theory has chosen our Procedural Code. recognizing when the process starts, it is also mentioned that judicial protection must be even before any process.